Detection and Determinants of Leptospira Infection in Rodents, Cattle, and Humans in Muheza District, Tanzania: A Call for One Health Approach - Gamba Gerald Manyama; Gerald Dickson Mlowe; Athumani Msalale Lupindu; Abdul Suleman Katakweba (Public Health Challenges)
ABSTRACT Interaction among humans, livestock, and wildlife plays an important role in zoonotic disease transmission. The emergence of Leptospira in humans, rodents, and cattle remains relatively understudied. A cross‐sectional study was conducted between February and May 2023 in Muheza to determine evidence of Leptospira infection and associated factors in rodents, cattle, and humans. A total of 479 serum samples from rodents (n = 201), humans (n = 198), and cattle (n = 80) were examined by microscopic agglutination test (MAT) to detect antibodies against 6 live Leptospira stock culture serovars, including Pomona, Hebdomadis, Canicola, Grippotyphosa, Sokoine, and Lora. Additionally, a questionnaire survey was conducted on 140 respondents to determine factors that are associated with Leptospira seropositivity. Descriptive statistics and Chi‐square test were used to analyze the data. The overall Leptospira seroprevalence in rodents, cattle, and humans was 6.0% (12/201; 95% CI: 3.12%–10.20%), 12.5% (10/80; 95% CI: 6.16%–21.79%), and 13.1% (26/198; 95% CI: 8.76%–18.65%), respectively, and the most predominant serovars were Grippotyphosa, Sokoine, and Hebdomadis. A significant difference in the seroprevalence was observed in occupation, whereby farmers were more likely to be infected with Leptospira than those in other occupations (χ2 = 9.19, df = 3, p = 0.027). This study showed co‐agglutination among rodents, cattle, and humans with serovars Hebdomadis, Sokoine, and Grippotyphosa. People aged 36–59 had the highest seropositivity, suggesting they are the most at‐risk group. This study shed light on pathogenic serovars circulating among humans, rodents, and cattle and factors associated with seropositivity. The findings appeal for multisectoral One Health approach for effective control of Leptospira infection and other zoonotic diseases.